Contributions of social capital to supply chain sustainability practices: Conceptual framework and propositions - Gustavo Picanço Dias; Minelle E. Silva; Fernando Luiz Emerenciano Viana (Cleaner Logistics and Supply Chain)
The integration of sustainability dimensions as part of supply chain management represents a constant challenge for companies. This happens because to address supply chain sustainability (SCS), companies need to know how collective behaviours are present in their supply chain practices (e.g. cooperation, coordination, collaboration). However, this is easier said than done. Therefore, through the lens of social capital theory (SCT), this paper elaborates on how SCS practices among supply chain members can enhance sustainability outcomes. Through an iterative theory-building process, we explored the integration between SCT and SCS in this conceptual paper. The argumentation shows that beyond direct causality relations employed, social capital can strengthen SCS practices to create value among supply chain members. This becomes possible through a combination of collaboration initiatives and supply chain learning. This paper contributes to the theory by offering a conceptual framework and a set of propositions for an alternative way to understand SCS practice. Additionally, this paper provides practical contributions by showing how managers can integrate sustainability into their daily operations.